TOWARD A PROCESS MODEL OF VENTURE CAPITAL EMERGENCE: THE ROLE OF DIFFUSION (INTERACTIVE PAPER) - Lingelbach, David C; Gilbert, Evan; Murray, Gordon (Babson, 2010)
We consider how venture capital (VC) industries emerge in limited access orders (LAOs; North, Wallis, and Weingast, 2009), focusing on the role of diffusion. Rumelt (1987) suggested that VC emerges when entrepreneurial firms require low levels of asset cospecialization and where expected returns occurs in the near future. This imperative for near-term returns is complicated in LAOs, where the first members of a VC population must act as institutional entrepreneurs in a context inimical to innovation and its challenge to elites’ economic rents, and requires rapid institutionalization. Diffusion—“the process in which an innovation is communicated through certain channels over time among the members of a social system” (Rogers, 2003)—plays a central role in the success of this process, which is based on force or domination mechanisms (Lawrence, Winn, and Jennings, 2001). In an LAO setting larger players are more likely to be successful institutional entrepreneurs (Greenwood, Suddaby, and Hinings, 2002), in part because they have the resources to exercise force or domination. In addition, both geographical proximity and efficacy increases the likelihood that corporate VC diffuses to new populations (Gaba and Meyer, 2008). We suggest that 1) VC emergence is an institutionalization process in which diffusion plays a central role, 2) rapid diffusion requires institutional entrepreneurs in this setting to acquire power in the presence of dominant elite coalitions, and 3) proximity and efficacy of other VC populations can facilitate this process.